(untitled) (Journal of Partial Differential Equations, 1999)
In this paper we study the scattering theory for the semilincar wave equation u_tt - Δu = F(u(t, x), Du(t, x)) in R^n (n ≥ 4) with smooth and small data. We show that the scattering operator exists for the nonlinear term F = F(λ) = O(|λ|^1, α), where α is an integer and satisfies α ≥ 2, n = 4; α ≥ I, n ≥ 5.